2013
DOI: 10.12968/bjon.2013.22.15.893
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors in MMR immunisation decision making

Abstract: Immunisation decision making is not a straightforward process for parents. Many factors influence parental decision making on whether they immunise their child with the measles, mumps and rubella (MMR) vaccine. The feasibility study described in this article provides insight into influencing factors associated with decisions regarding the immunisation of children by parents. The study findings suggest that the practice nurse is a credible source of information for parents seeking informed decision making. At a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
9
1
1
Order By: Relevance
“…It became apparent from this study that the attitude of health care providers had an influence on the mothers' decisions to immunise their children. The value of good health professional advice is also described by Hill (2013), who demonstrated that health professionals are seen as a trustworthy source of information, and that parents are reported to actively seek their advice to inform their decision about whether to immunise their children or not.…”
Section: The Influence Of the Attitudes Of Health Care Providersmentioning
confidence: 99%
See 1 more Smart Citation
“…It became apparent from this study that the attitude of health care providers had an influence on the mothers' decisions to immunise their children. The value of good health professional advice is also described by Hill (2013), who demonstrated that health professionals are seen as a trustworthy source of information, and that parents are reported to actively seek their advice to inform their decision about whether to immunise their children or not.…”
Section: The Influence Of the Attitudes Of Health Care Providersmentioning
confidence: 99%
“…Immunisation is stated to be the most effective public health intervention in the world for saving lives and for promoting good health. Immunisation is also an intervention that saves money (Hill, 2013). The Expanded Programme on Immunisation (EPI) Fact Sheet states that, "According to WHO every dollar spent on vaccine saves seven dollars in medical costs and 25 dollars in overall costs related to vaccine preventable diseases" (WCDoH, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Paling tidak sekitar 90% anak harus mendapat imunisasi campak rutin dan pemberian vitamin A, untuk mencapai tujuan tersebut. Faktor yang mempengaruhi seseorang untuk imunisasi campak terdapat 7 yaitu sejarah imunisasi, lokasi dan akses ke pelayanan kesehatan, hubungan dengan profesionalitas dalam dunia kesehatan, persepsi dari sumber informasi, Faktor risiko dengan vaksin, kelas sosial dan etnis (Hill & Cox, 2013)…”
Section: Kejadian Campak DI Kecamatanunclassified
“…[21] In the past, nurses have played a major role in improving childhood vaccinations against other infectious diseases through nurse-administered programs or by influencing parents. [22][23][24] Equipped with updated HPV-vaccine knowledge, nurses can better educate and empower parents for timely HPV vaccinations. Various educational strategies in healthcare practice or community settings have shown to be effective in improving parental HPV vaccine knowledge and uptake.…”
Section: Introductionmentioning
confidence: 99%